Clinical and economic impact of coronary artery bypass graft and percutaneous coronary intervention in young individuals with acute coronary syndromes and multivessel disease: A real-world comparison in a middle-income country - Gustavo de Almeida Alexim; Gustavo de Almeida Alexim; Gustavo de Almeida Alexim; Luiza Ferreira Rocha; Luiza Ferreira Rocha; Giovani Prediger Dobri; Giovani Prediger Dobri; Adair da Silva Rosa Júnior; Ricardo Torres Bispo Reis; Ana Claudia Cavalcante Nogueira; Ana Claudia Cavalcante Nogueira; Ana Claudia Cavalcante Nogueira; et al. (Frontiers in Cardiovascular Medicine, 2022)
BackgroundIn recent decades, the world watched a dramatic increase in the incidence of acute coronary syndromes (ACS) among young individuals (≤55 years-old) and a relative decrease in the elderly. The management of ACS in young patients with multivessel disease still needs to be elucidated, as these individuals maintain a long life expectancy.Research QuestionTo compare clinical outcomes and care costs in individuals with premature ACS and multivessel disease undergoing coronary artery bypass graft surgery (CABG) or percutaneous coronary intervention (PCI).Methods and ResultsParticipants included all individuals ≤55 years-old admitted with ACS to public hospitals in Brasília (Brazil) between 2013 and 2015 and who underwent cardiac catheterization with SYNTAX score ≥23 or Duke category 6. Outcomes were adjudicated with death certificates and data from medical records. The primary outcome was the occurrence of major adverse cardiovascular events (MACE), defined as death due to cardiovascular causes, recurrent hospitalizations due to cardiovascular ischemic events, and incident heart failure New York Heart Association III-IV. As secondary outcome we assessed indirect and direct costs by evaluating the cost of lost productivity (in international dollars (Int$) per year) due to illness and death, outpatient costs and costs with new hospitalizations. Multivariate and principal components (PC) adjusted analyzes were performed.ResultsAmong 1,088 subjects (111 CABG and 977 PCI) followed for 6.2 years (IQR: 1.1), 304 primary events were observed. MACE was observed in 20.7% of the CABG group and 28.8% of the PCI group (p = 0.037). In multivariate analyses, PCI was associated with a hazard ratio (HR) = 1.227 (95% CI: 1.004–1.499; p = 0.0457) for MACE, and in PC-adjusted HR = 1.268 (95% CI: 1.048–1.548; p = 0.0271) compared with CABG. Despite direct costs were equivalent, the cost due to the loss of labor productivity was higher in the PCI group (Int$ 4,511 (IQR: 18,062)/year vs Int$ 3,578 (IQR: 13,198)/year; p = 0.049], compared with CABG.ConclusionsAmong young individuals with ACS and multivessel disease, surgical strategy was associated with a lower occurrence of MACE and lower indirect costs in the long-term.